Rules of Thumb - Silverman Jay (MC Graw Hill, 2008)
Brevity and practicality are the hallmarks of Rules of Thumb. Reflecting the most current APA documentation styles, the APA Update Edition, 7/e remains the ideal handbook for improving grammar without overwhelming student writers with specialized terminology.